2021
DOI: 10.3390/pharmaceutics13020250
|View full text |Cite
|
Sign up to set email alerts
|

A New Surface Charge Neutralizing Nano-Adjuvant to Potentiate Polymyxins in Killing Mcr-1 Mediated Drug-Resistant Escherichia coli

Abstract: Resistance to polymyxins when treating multidrug-resistant (MDR) Gram-negative bacterial infections limit therapeutic options. Here, we report the synthesis of a nickel (Ni) doped Zinc oxide (NZO) combined with black phosphorus (BP) (NZB) nanocomposite and its synergistic action with polymyxin B (PolB) against polymyxin-resistant Escherichia coli harboring mobilized colistin resistance (mcr-1) gene. NZB and PolB combination therapy expressed a specific and strong synergy against Mcr-1 expressing E. coli cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…Another study found that when MDR S. aureus is exposed to near-infrared light, Au–ZnO coupled with black phosphorus suppresses its growth. 17 Cho et al 18 reported the antibacterial activity of nickel doped zinc oxide conjugated black phosphorus nanocomposite and its synergistic activity with polymyxin B against polymyxin-resistant E. coli carrying colistin resistance gene mcr-1 and found that the nanocomposite was biocompatible with HEK293 cells and polymyxin B. Several studies have been conducted in-depth to explore the unusual characteristics of Ni-Cu ferrites and it was concluded that these characteristics are due to favoured distributions of Fe 3+ and Fe 2+ cations into the tetrahedral and octahedral sub-lattice sites in the crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that when MDR S. aureus is exposed to near-infrared light, Au–ZnO coupled with black phosphorus suppresses its growth. 17 Cho et al 18 reported the antibacterial activity of nickel doped zinc oxide conjugated black phosphorus nanocomposite and its synergistic activity with polymyxin B against polymyxin-resistant E. coli carrying colistin resistance gene mcr-1 and found that the nanocomposite was biocompatible with HEK293 cells and polymyxin B. Several studies have been conducted in-depth to explore the unusual characteristics of Ni-Cu ferrites and it was concluded that these characteristics are due to favoured distributions of Fe 3+ and Fe 2+ cations into the tetrahedral and octahedral sub-lattice sites in the crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of nanocarriers and peptides can inhibit the growth of bacteria strains that are resistant to last-resort antibiotics and achieve the purpose of treating infections. Nickel-doped zinc oxide combined with black phosphorus nanocomposite with active peptide polymyxin B could be used against E. coli resistant to last-resort antibiotic polymyxin [ 220 ]. As AMPs are becoming more widely and intensively researched, more investments and further studies about combining peptides with nanodelivery systems are likely to be a future study hotspot in medicine.…”
Section: Conclusion and Challenges In Nanotechnology For Amp Deliverymentioning
confidence: 99%
“…NPs are becoming a potential therapy for treating diseases such as bacterial infections caused by resistance to currently available antibiotics; such resistance is one of the most serious issues threatening human health worldwide [11,79,80]. Several properties of NPs, including large surface-area-to volume ratio, small size, modification of target ligand, and cost effectiveness, serve as advantages for their use as alternative agents to resolve current antibiotic-related challenges [81].…”
Section: Inner Core Npsmentioning
confidence: 99%